Radical-mediated dehydrative preparation of cyclic imides using (NH4)(2)S2O8-DMSO: application to the synthesis of vernakalant - Garad, Dnyaneshwar N.; Tanpure, Subhash D.; Mhaske, Santosh B. (Beilstein Journal of Organic Chemistry, 2015)
Ammonium persulfate-dimethyl sulfoxide (APS-DMSO) has been developed as an efficient and new dehydrating reagent for a convenient one-pot process for the synthesis of miscellaneous cyclic imides in high yields starting from readily available primary amines and cyclic anhydrides. A plausible radical mechanism involving DMSO has been proposed. The application of this facile one-pot imide forming process has been demonstrated for a practical synthesis of vernakalant.
Keywords: APS-DMSO; imides; practical synthesis; radical-mediated; vernakalant

Radical beckmann rearrangement and its application in the formal total synthesis of antimalarial natural product isocryptolepine via C-H activation - Mahajan, Pankaj S.; Humne, Vivek T.; Tanpure, Subhash D.; Mhaske, Santosh B. (Organic Letters, 2016)
The Beckmann rearrangement of ketoximes, mediated by ammonium persulfate-dimethyl sulfoxide as a reagent, has been achieved under neutral conditions. Based on the radical trapping and O-18-labeling experiments, the transformation follows a mechanism involving a radical pathway. The scope and generality of the developed protocol has been demonstrated by 19 examples. The developed protocol and Pd-catalyzed intramolecular double C-H activation were used as key steps in the formal total synthesis of antimalarial natural product isocryptolepine.

Ruthenium-catalyzed regioselective alkenylation/tandem hydroamidative cyclization of unmasked quinazolinones using terminal alkynes - Viveki, Amol B.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2018)
Ruthenium-catalyzed amide directed C-sp2-H activation of the quinazolinone scaffold has been demonstrated, leading to the selective mono- or dialkenylation in moderate to good yields to achieve medicinally important stilbene containing quinazolinones. The terminal allcyne is utilized as a coupling partner, which resulted in the selective trans-alkene formation. Electron-deficient phenylacetylenes facilitate alkenylation followed by tandem hydroamidation of the newly generated trans double bond to provide novel quinazolinone alkaloids related to the Luotonine class of natural products.

Ru-catalyzed regioselective cascade annulation of acrylamides with 2-alkynoates for the synthesis of various 6-Oxo nicotinic acid esters - Garad, Dnyaneshwar N.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2019)
Ru-catalyzed regioselective cascade annulation of acrylamides with 2-alkynoates via aza-Michael/C-H activation sequence for the synthesis of various 6-oxo nicotinic acid esters is described. The regioselectivity of the protocol has been confirmed by performing silver mediated protodecarboxylation of the corresponding 6-oxo nicotinic acid to furnish 2-pyridone. The developed protocol is copper or silver salt-free and uses inexpensive, safe, and environmentally benign peroxide-based ``oxone'' as the sole oxidant. A redox-neutral version of the protocol is also demonstrated.

Regio- and stereoselective construction of 1,3,5-triaroylcyclohexanes via KO t Bu-mediated cyclotrimerization of aryl vinyl ketones - Mahale, Sachin D.; Yadav, Vinita; Gonnade, Rajesh G.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2024)
Herein, we disclose a simple one-pot method for an efficient regio- and stereoselective synthesis of 1,3,5-triaroylcyclohexanes from aryl vinyl ketones using potassium tert-butoxide. The developed protocol allows the construction of various symmetrically substituted cyclohexanes in good to excellent yields. The major product 2 also can be converted to the product 3 (all equatorial) conveniently by acid catalysis. This protocol features a good substrate scope and functional group compatibility.